Impulsivity is associated with firing regularity in parkinsonian ventral subthalamic nucleus. Issue 4 (2nd March 2022) - Vissani, Matteo; Micheli, Federico; Pecchioli, Guido; Ramat, Silvia; Mazzoni, Alberto
Abstract: Impulsive–compulsive behaviors (ICB) are over‐represented in Parkinson's disease (PD) patients. Neurons in the ventral subthalamic nucleus (STN) might play a predominant role in the modulation of impulsivity. We characterized the firing regularity of 742 subthalamic neurons from 24 PD patients (12 ICB+ and 12 ICB‐) in an OFF medication state. We computed the firing regularity in the dorsal and ventral STN regions, and we compared their performance in discriminating ICB patients. Regularity of ventral neurons in ICB+ patients is higher and supports a significant discrimination between the two cohorts. These results substantiate a ventral location of neurons involved in impulsivity.